2013
DOI: 10.1111/jai.12250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-dose vitamin C supplementation on growth, tissue ascorbic acid concentrations and physiological response to transportation stress in juvenile silver pomfret, Pampus argenteus

Abstract: Summary This study investigated the effect of high‐dose vitamin C supplementation on growth, tissue ascorbic acid concentrations and physiological response to transportation stress in juvenile silver pomfret, Pampus argenteus (initial average weight 6.2 ± 0.2 g). Three practical diets were formulated to contain 100 (control), 450 and 800 mg ascorbic acid/kg diet, respectively, supplied as l‐ascorbyl‐2‐polyphosphate. Each diet was fed to triplicate groups of fish in circular tanks (3 m ø, 1.5 m depth) (60 fish/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
1
20
1
Order By: Relevance
“…Hence, vitamin C supplementation in weaning piglets can increase immunoglobulin concentration (Zhao et al, 2002;Lauridsen and Jensen, 2005) and improve performance parameters (Bekenev et al, 2015). It was found that vitamin C is able to reduce stress effects in fish (Peng et al, 2013) and chicken (Chand et al, 2014). However, in weanling piglets there were only some or no beneficial effects (Mahan and Saif, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, vitamin C supplementation in weaning piglets can increase immunoglobulin concentration (Zhao et al, 2002;Lauridsen and Jensen, 2005) and improve performance parameters (Bekenev et al, 2015). It was found that vitamin C is able to reduce stress effects in fish (Peng et al, 2013) and chicken (Chand et al, 2014). However, in weanling piglets there were only some or no beneficial effects (Mahan and Saif, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplements are commonly used in aquaculture for a wide variety of reasons including stress reduction (Peng et al . ; Vallejos‐Vidal et al . ), improving specific and nonspecific immune resistance (Wang et al .…”
Section: Can We Prepare Fish For Transportation Stress?mentioning
confidence: 99%
“…Dietary supplements are commonly used in aquaculture for a wide variety of reasons including stress reduction (Peng et al 2013;Vallejos-Vidal et al 2016), improving specific and nonspecific immune resistance (Wang et al 2006;Vallejos-Vidal et al 2016), enhancing colouration (Pan & Chien 2009;Kouba et al 2013) and increasing growth rate (Vallejos-Vidal et al 2016). Therefore, prior to transport, there is the opportunity to use dietary supplements to enhance the immune system and improve stress tolerance (Volpatti et al 1998;Lim et al 2002;Rollo et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations